OS EFEITOS DA MP 579/2012 SOBRE OS FATORES DETERMINANTES DA ESTRUTURA DE CAPITAL DAS EMPRESAS QUE COMPÕEM O ÍNDICE DE ENERGIA ELÉTRICA LISTADAS NA B3 - Ferrari, Emerson Orsini (2022)
The objective of this study was to verify the determining factors of the capital structure of companies, which are part of the Electric Energy Index (IEE) listed on B3 in the period from 2006 to 2020, and if they showed any variability after the issuance of the Provisional Measure 579/2012. We also sought to verify whether these determinants are statistically significant to explain indebtedness and, finally, whether they were consistent with the assumptions of the Information Asymmetry, Agency Costs, Trade-off and Pecking Order theories. The study had a quantitative approach, descriptive procedure, we sought to study the existence of a structural break in the behavior of the determining factors, through Chow's F Test and, also, through the t Test of paired mean comparison. A linear regression model was made, with panel data, containing a sample of the 19 companies of the Electric Energy Index listed on B3, whose data from the companies' financial statements were collected through the Bloomberg® platform, in addition to consultations on the websites of the companies. The data were organized in the form of a Microsoft Office Excel365® spreadsheet in order to perform the analyzes using the R Studio software. The Chow F tests and the t Test for paired means confirmed that there was no structural break after the issuance of MP 579/2012, it was identified that the parameters remained the same during the time of the study, rejecting the hypothesis that MP 579 /2012 influenced the determining factors of the capital structure of companies that make up the Electric Energy Index in this period. The study showed that companies with greater availability of internal resources, therefore more liquid from the point of view of liquidity, with a greater amount of physical assets and that have a higher rate of return, assume the tendency of not getting into debt, in order to approach the assumptions of the Pecking Order theory. It was also noted that these companies had as determining factors of the capital structure statistically significant Current Liquidity, Tangibility, Return on Assets, Firm Size, Business Risk and Profitability, only the Opportunity for Growth was not statistically significant. . By aligning themselves with the Pecking Order, companies demonstrate that, preferably, they will use internal to external resources for new investments, therefore, they will have characteristics of being less leveraged.